Theoretical Computer Science 6th IFIP TC 1/WG 2.2 International Conference, TCS 2010, Held as Part of WCC 2010, Brisbane, Australia, September 20-23, 2010. Proceedings - Calude, Cristian S.; Sassone, Vladimiro; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 6th FIP WG 2.2 International Conference, TCS 2010, held as a part of the 21th World Computer Congress, WCC 2010, in Brisbane, Australia, in September 2010. The 23 revised full papers presented, together with 4 invited talks, were carefully reviewed and selected from 39 submissions. TCS 2010 deals with topics focused at but not limited to algorithms, complexity, models of computation, logic, semantics, specification and verification, power-awareness issues in wireless networks, data mining, knowledge discovery, multiprocessor issues as well as AI issues.
Convexity, Duality and Effects -- A Calculus for Power-Aware Multicast Communications in Ad Hoc Networks -- The Coarsest Precongruences Respecting Safety and Liveness Properties -- Entropy and Attack Models in Information Flow -- Safe Equivalences for Security Properties -- On Probabilistic Alternating Simulations -- Probabilistic Mobility Models for Mobile and Wireless Networks -- On Packing Splittable Items with Cardinality Constraints -- Deterministic Computations in Time-Varying Graphs: Broadcasting under Unstructured Mobility -- Slicing Behavior Tree Models for Verification -- Optimization of the Anisotropic Gaussian Kernel for Text Segmentation and Parameter Extraction -- Online Dictionary Matching for Streams of XML Documents -- The Duality of Computation under Focus -- Polarized Resolution Modulo -- A Logic on Subobjects and Recognizability -- Terminating Tableaux for with Number Restrictions on Transitive Roles -- Proof System for Applied Pi Calculus -- Concurrent Pattern Calculus -- Initial Segment Complexities of Randomness Notions -- Topologies Refining the Cantor Topology on X ? -- On Symbolic Representations of Maximum Matchings and (Un)directed Graphs -- Traceable Sets -- Approximating the Non-contiguous Multiple Organization Packing Problem -- Improving the Competitive Ratios of the Seat Reservation Problem -- A Semiring-Based Trace Semantics for Processes with Applications to Information Leakage Analysis -- A Game-Theoretic Approach to Routing under Adversarial Conditions -- An Operational Model for Multiprocessors with Caches.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Logic design; Computer Science; Algorithm Analysis and Problem Complexity; Logics and Meanings of Programs; Computation by Abstract Devices; Software Engineering; Computer Communication Networks; Mathematical Logic and Formal Languages